Method for preparation of amorphous, anhydrous crystalline or hydrated crystalline docetaxel - Pyo, Sang-Hyun; Cho, Jin-Suk; Kim, Moon‐Suk; Song, Bong-Kyu; Choi, Ho-Joon (2012)
This invention is directed to a method for the preparation of docetaxel having an amorphous, anhydrous crystalline, or hydrated crystalline structure. In accordance with the invention, highly pure amorphous, anhydrous crystalline, or hydrated crystalline docetaxel can be produced with a high yield by using a solvent precipitation method, colloid formation method, etc.